Implementasi Gaya Kepemimpinan Situasional Kepala Sekolah di Sekolah Menengah Pertama - Anis Mahatika; Suswati Hendriani (J-MPI (Jurnal Manajemen Pendidikan Islam), 2022)
The purpose of this research is to describe the situational leadership style of the principal at SMP Negeri 5 Batusangkar. The type of research used in this study is a phenomenological type with a qualitative approach. Data collection in this study used the methods of observation, interviews, and documentation studies. Then to analyze the data, the researcher uses the Miles Huberman model technique, which consists of data reduction, data presentation, verification, and conclusion drawing. Based on the results of the study, the situational leadership style of the principal at SMP Negeri 5 Batusangkar is carried out by 1) applying the telling model of situational leadership by giving tasks to work partners using one-way communication; 2) applying the situational leadership selling model using two-way communication so that communication can be established better to provide the right direction to work partners. 3) applying the participating model situational leadership in which the orientation of the principal's leadership is not only a task carried out by subordinates but also maintaining good relationships and making decisions together so that they can be accounted for together as well; 4) apply the situational leadership model of delegating to partners who are able and can carry out the assigned tasks.